The fibroblast growth factor family: involvement in the regulation of folliculogenesis - Chaves, Roberta Nogueira; Tavares de Matos, Maria Helena; Buratini, Jose [UNESP]; de Figueiredo, Jose Ricardo (CSIRO Publishing, 2012)
Several growth factors have been identified as local regulators of follicle development and ovulation. Fibroblast growth factor (FGF) family members are potent mitogens and are involved in cell differentiation, cell migration and angiogenesis in many tissues and organs. In addition to FGF-2, which is the most-studied FGF, other important members are FGF-1, -5, -7, -8, -9 and -10. A number of studies have indicated that FGFs play important roles in regulating the initiation of primordial follicle growth, oocyte and follicle survival, granulosa and theca cell proliferation and differentiation, corpus luteum formation, steroidogenesis and angiogenesis. The purpose of this review is to highlight the importance of the FGFs on mammalian female reproduction, providing a better understanding of the roles of this family in ovarian physiology and female fertility.
Keywords: culture medium; development; follicles; ovary; survival